VIEWER'S EMOTIONS ON RUSSIA-UKRAINE CONFLICT REPORT BY FOX NEWS AND HINDUSTAN TIMES CHANNEL. - Elviana, Riski Elviana Eka Suci (Faculty of Social and Political Sciences University of Bangka Belitung, 2025)
This study aims to determine viewers' emotional responses to the Russia-Ukraine conflict as expressed in YouTube comments on news reports by Fox News and Hindustan Times. Using Martin & White's (2005) Appraisal Theory, specifically the affect subsystem, the study analyzed how viewers expressed emotions such as happiness, unhappiness, security, insecurity, satisfaction, dissatisfaction, inclination, and disinclination. The findings revealed the predominance of negative sentiments, especially unhappiness, reflecting outrage and moral condemnation of Russia's military actions, including the attack on the children's hospital. Support for Ukraine was evident through expressions of solidarity and calls for international intervention. Meanwhile, pro-Russian narratives are often dismissed as propaganda. This research examines how internet debates have become more heated and divided due to global political conflicts. Wars are fought not only on the ground, but also in the hearts and minds of internet users.